Hubungan Motivasi Terhadap Prestasi Partisipan Didik di SMP Poso Kota Utara - Muhdin, Nining Kasim; Aras, Muhamad (Jurnal Biologi Babasal, 2024)
Abstract : This study aims to identify the relationship between motivation and student achievement at North Poso City Middle School. The research was carried out at SMP Negara 2 Poso, Poso Kota District, Poso Regency by taking 105 students as illustration objects based on Isaac and Michael's theory of determining the number of illustrations with an error rate of 5% from the total population of 147 students. The research procedure used in this research is quantitative research. The information collection method used is a questionnaire or questionnaire. Questionnaires are used to obtain information about learning motivation influencing student learning achievement results. Analysis of the information shows that motivation ( There is also a hypothesis test result that has been produced, Sig( 0,00) & lt; alpha (0.005), so there is a significant relationship between motivation and student achievement at North Poso City Middle School